Application design and assessment of a novel small-decentralized solar distillation device based on energy, exergy, exergoeconomic, and enviroeconomic parameters. (February 2021) - Fang, Shibiao; Mu, Lin; Tu, Wenrong
Abstract: In this paper, a novel small-decentralized desalination device is presented for increasing the temperature difference between brackish water and glass cover, so as to enhance the solar still's freshwater productivity. This novel solar still device is based on installing a lens in front of the single slope solar still, and two lenses on still's both sides, and a reflector over the back side of the solar still. The main objective of such novel still is to concentrate sunrays at the still's bottom basin, through the refraction function of Fresnel lens. Furthermore, this novel still makes the reflector transferring its reflected sunrays to the solar still's basin. Experiments are conducted under the climate conditions in Hangzhou city, China, for testing the novel still's operational performance, and internal heat and mass transfer characteristics. Assessment of the novel still's feasibility is performed based on energy, exergy, exergoeconomic, and enviroeconomic methodologies, as well as energy payback time. Results show that the productivity of novel still is 32% higher than that of conventional still, and novel solar still enhances the average hourly energy efficiency by 97.73%, compared to conventional solar still. While, the corresponding value of hourly exergy efficiency is also enhanced by 43.713%. Due to the higher energy and exergy outputs of novel still throughout its lifetime, the novel solar still proposed in this study mitigates more CO2 compared to the conventional still. Overall, incorporation three lenses and one reflector with the still is found promising in terms of freshwater yield, cost, and energy payback time compared to conventional one. Exergoeconomic and environmental parameters of the novel solar still are found more effective compared to the conventional one. Highlights: A novel solar still with lenses and reflector is developed and evaluated. Using lenses and reflector increases still's productivity by about 32%. Novel solar still enhances the average hourly energy efficiency by 97.73%. Novel still mitigates more CO2 compared to conventional one based on energy & exergy. Novel solar still's enviroeconomic and exergoenvironmental are 324.317 $ and 22.148 $.